An experimental investigation on the burning behaviors of lithium ion batteries after different immersion times. (1st January 2020) - Tao, Changfa; Ye, Qingpan; Wang, Chunmei; Qian, Yejian; Wang, Chenfang; Zhou, Taotao; Tang, Zhiguo
Abstract: The seawater immersion test is an important indicator of the lithium ion batteries (LIBs) safety, and the fire behavior of LIBs is affected by immersion time t im . In this study, 3.5 wt% NaCl solution as surrogate seawater is used to perform LIBs immersion test. Several parameters are measured to evaluate the fire hazards of LIBs, such as ignition time t ig, surface temperature, mass loss, heat release rate and total heat release. The fire hazards of batteries immersed under different t im is assessed by a conical calorimeter. The experimental results demonstrate that t ig reaches a minimum value when t im is 3 h, and t ig changes slightly with further increase of t im . The heat release rate reaches a maximum value when t im is 3 h for 100% stages of charge (SOC), and 2 h for 50% SOC. The ejection temperature T ej remains constant with the increase in t im, while the maximum temperature T max decreases with the increase in t im . Graphical abstract: Image 1 Highlights: The burning behaviors of 18650 LIBs after different immersion times are investigated. The safety valve can be damaged by the salt water after a long time immersion. The battery ignition time is influenced seriously with the increase of the immersion time. The total mass loss decreases with the increase in the immersion time. There are peak values for total heat release and heat release rate with the immersion time of 3 h for 100% SOC.